(untitled) (Palimpsesto, 2025)
The article analyzes eight institutions for people with disabilities located in the northern region of Greater Buenos Aires (Argentina), which offer services and activities in various fields. The research was based on interviews with professionals working in these institutions and a review of their institutional websites. It is observed that the notion of care is not explicitly part of the institutional functions, but rather emerges as a tacit or latent component of the professionals’ work. However, care assumes a prominent role in interactions with the families of people with disabilities, where women/mothers are recognized as the primary caregivers.